Patients' satisfaction with the bulk trolley system in a government hospital in Malaysia - Jamaluddin, Rosita; Abd Manan, Nurul Aqmaliza; Basri, Aina Mardiah; Abdul Karim, Muhammad Shahrim (Emerald Group Publishing, 2010)
Purpose: The purpose of this paper is to determine patients' satisfaction with the bulk trolley food service system and the effect of the system on energy and protein intakes.